2011
DOI: 10.1002/pc.21139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of modified mica on mechanical and durability properties of FRP composite materials for civil engineering

Abstract: The durability of fiber reinforced polymer (FRP) composite materials in humid and harsh environments is an important consideration for acceptance of these materials in civil engineering applications. Reducing the moisture ingress may improve the durability of FRPs. The addition of modified inorganic powder, such as clay nanoparticles, may improve several important properties of polymers, such as barrier properties, fire retardancy, dimensional stability, and mechanical strength. The present work aims to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In these studies, functionalized NC decreases D by significantly increasing the water uptake since NC is highly hydrophilic, even with high NC and/or modified NC loading (up to 5 wt%). 48 Absorbed water leads to swelling, plasticization, and hydrolysis of the polymer matrix, affecting the durability of the polymer whereas GO prevents these phenomena without affecting the initial rate of diffusion or D at long time. 49…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, functionalized NC decreases D by significantly increasing the water uptake since NC is highly hydrophilic, even with high NC and/or modified NC loading (up to 5 wt%). 48 Absorbed water leads to swelling, plasticization, and hydrolysis of the polymer matrix, affecting the durability of the polymer whereas GO prevents these phenomena without affecting the initial rate of diffusion or D at long time. 49…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, GFRP based marine and civil structures have proven to be a suitable alternative to the conventional steel based structures, owing to their economic and environmental benefits. [1,2] Despite being increasingly used for both naval constructions and offshore and oceanographic purposes, the durability of such composites when exposed to different marine conditions is still a subject of research. GFRP composites when exposed to water, moisture, heat, and other hostile seawater environments have demonstrated physicochemical changes, which hamper their structural integrity, ultimately resulting in the deterioration of in-service performance and shortening of service-life.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of the mechanical properties was attributed to enhanced durability and chemical stability of the nanoparticles, and blocking of the alkaline solution penetration by the nanoparticles. Robert et al [24] investigated the effect of the addition of modified mica on FRP properties. They found that the addition of 3% of 3-aminopropyltriethoxysilane (APS)or octyldecylamine (ODA)-mica leaded to an increase of ∼25% of the ultimate tensile strength, and an increase of 27% and 29% of the tensile modulus of elasticity for APS-and ODA-mica, respectively.…”
Section: Introductionmentioning
confidence: 99%